Distinctions in Fine-Scale Spatial Genetic Structure Between Growth Stages of Picea jezoensis Carr. - Kitamura, Keiko; Nakanishi, Atsushi; Lian, Chunlan; Goto, Susumu (Frontiers in Genetics, 2018)
Conifers in northern forests, such as fir and spruce, preferably regenerate on coarse woody debris, including fallen logs, stumps, and snags. In northern Japan, the sub-boreal conifer species Picea jezoensis is completely dependent on coarse woody debris for seedling establishment. To understand the fine-scale spatial genetic structure of this species, a 5-ha plot was established in central Hokkaido, and 531 individual trees were categorized into four life-stages (seedling, sapling, juvenile, and mature) on the basis of age and size. The fine-scale spatial genetic structure of the established seedlings and later growth stages was investigated using 11 nuclear simple sequence repeat loci. A STRUCTURE analysis of seedlings and saplings established on fallen logs revealed that genetically related individuals were spatially localized between adjacent logs. We also found a significant fine-scale spatial genetic structure in early life-stages based on a decline in the kinship coefficient calculated between individuals over shorter to longer spatial distances. Furthermore, the estimation of dispersal kernels indicated the frequent occurrence of short-distance seed dispersal. These results indicated that genetically related seedlings and saplings regenerated on the same or nearby fallen logs. In contrast to the results for the early stages, mature-stage trees showed no significant fine-scale spatial genetic structure. We ran a simulation to examine the hypothesis that the fine-scale spatial genetic structure could be eliminated by demographic thinning during life history processes. We calculated values for simulated offspring generated under three sets of conditions; i.e., by removing (i) inbred individuals, (ii) randomly chosen individuals, and (iii) all individuals on the specific fallen logs. However, the results for the fine-scale spatial genetic structure were significant for all simulated data sets. This indicated that inbreeding depression, stochastic loss, or eradication of establishment sites by local disturbances alone could not explain the lack of fine-scale spatial genetic structure among mature-stage trees. Therefore, it is possible that the colonization history of mature trees present on the study site might differ from that of the current offspring.